First description of Streptococcus lutetiensis from a diseased cat. (7th June 2019) - Piva, S.; Pietra, M.; Serraino, A.; Merialdi, G.; Magarotto, J.; Giacometti, F.
Abstract: This paper describes for the first time the isolation of Streptococcus lutetiensis in a cat with intestinal lymphoma. The Streptococcus bovis group has undergone significant taxonomic changes over the past two decades and, in 2002, Poyart et al. described two distinct novel species within the genus Streptococcus : Streptococcus lutetiensis and Streptococcus pasteurianus . The bovis group streptococci include commensal species and subspecies or opportunistic pathogens of humans and animals. The cat was referred to the Veterinary Teaching Hospital, University of Bologna for chronic diarrhoea associated with fresh blood. A diagnosis of intestinal lymphoma was advanced. S. lutetiensis was accidentally isolated from the faeces of the cat and identified through MALDI‐TOF and 16s rRNA sequencing. The Kirby‐Bauer test revealed that the isolate was resistant to enrofloxacin, erythromycin, clindamycin, marbofloxacin and tetracycline. The detection of S. lutetiensis in cat faeces might suggest that it could be a normal inhabitant of cat intestinal tract or that it could be involved in the manifestation of intestinal diseases. Since bacteria belonging to the S. bovis group are considered emerging pathogens, additional research is required to evaluate the role of S. lutetiensis in cats and its role in the transmission of antimicrobial resistance. Significance and Impact of the Study: In this study the isolation of Streptococcus lutetiensis from a cat with intestinal lymphoma was described for the first time. An antimicrobial susceptibility test performed by means of the disc diffusion method revealed that the isolate was resistant to enrofloxacin, erythromycin, clindamycin, marbofloxacin and tetracycline. Nowadays the ecological or pathogenetic role of S. lutetiensis in the gut of animals remains unclear but, even if its role as commensal bacterium was confirmed, the presence of multi‐resistant S. lutetiensis in cat gut could favour the transmission of antimicrobial resistance to other bacteria. Abstract : Significance and Impact of the Study : In this study the isolation of Streptococcus lutetiensis from a cat with intestinal lymphoma was described for the first time. An antimicrobial susceptibility test performed by means of the disc diffusion method revealed that the isolate was resistant to enrofloxacin, erythromycin, clindamycin, marbofloxacin and tetracycline. Nowadays the ecological or pathogenetic role of S. lutetiensis in the gut of animals remains unclear but, even if its role as commensal bacterium was confirmed, the presence of multi‐resistant S. lutetiensis in cat gut could favour the transmission of antimicrobial resistance to other bacteria.